2005
DOI: 10.1007/bf03325889
|View full text |Cite
|
Sign up to set email alerts
|

Specific methanogenic activity of halophilic and mixed cultures in saline wastewater

Abstract: ABSTRACT:Wastewater containing high concentrations of salt, are difficult to treat using biological treatment processes, especially anaerobic processes. Limited information is available on methanogenic activity in saline environments. The objective of this research was to investigate the activity of halophilic methanogens, digester sludge and a mixed culture of halophilic and methanogenic bacteria, at various levels of salinity, in terms of lag period and specific methanogenic activity (SMA) at two temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 5 publications
1
14
0
Order By: Relevance
“…Chlorides are toxic to methanogenic microorganisms; they induce cell plasmolysis (an increase in the osmotic pressure and a consequent breakup of cells), and this effect has been studied by Riffat and Krongthamchat (2006).…”
Section: Efficiency Of the Removal Of Solids And Codmentioning
confidence: 99%
“…Chlorides are toxic to methanogenic microorganisms; they induce cell plasmolysis (an increase in the osmotic pressure and a consequent breakup of cells), and this effect has been studied by Riffat and Krongthamchat (2006).…”
Section: Efficiency Of the Removal Of Solids And Codmentioning
confidence: 99%
“…Although the results have shown that the addition of glycerol may favorably contribute for anaerobic process co-digestion, authors generally agree that different substrates must be combined under strict control due to initial organic load increase and mixture content of inhibitory as well as elements toxic to microorganism metabolism [9][10][11]. Carmona et al [12] and Viana et al [13] report that glycerol may present up to 46 g chloride/L, while a concentration between 5 and 9 g chloride/L is considered inhibitory for methanogenesis [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In many studies, the treatment technology for high salt or saline effluent has been studied for COD removal in laboratory scale digesters and pilot scale digesters [3][4][5][6][7][8][9][10][11][12] . Sodium ions (Na + ) appears to be essential for methanogenic bacteria due to its roles in a chemiosmotic coupling mechanism and 230 mg Na + L −1 or 10 mM was suggested as the optimal concentration for acetolastic methanogens in waste treatment process [3] .…”
Section: Introductionmentioning
confidence: 99%